All the Kremlin's men : inside the court of Vladimir Putin - Zygarʹ, Mikhail, 1981- (PublicAffairs, 2016)
"Charting the transformation of Vladimir Putin from a passionate fan of the West and a liberal reformer into a hurt and introverted outcast, All the Kremlin's Men is a historical detective story, full of intrigue and conspiracy. This is the story of the political battles that have taken place in the court of Vladimir Putin since his rise to power, and a chronicle of friendship and hatred between the Russian leader and his foreign partners and opponents..."--